Relation of technology acceptance towards intention to contribute cash waqf: investigation of three selected states in Malaysia - Wan Ismail, Wan Musyirah; Abdul Rasool, Mohamed Saladin (2023)
Technology plays an important role in increasing the financial sector efficiency. Through technology, it provides better experience and convenience for users. Economically, many payment services, banking industries and financial regulations have applied new technologies in their operations. Due to the lack of cash waqf collection in Malaysia, technology could be important aspect for the researcher to study its effectiveness in overcome the issue. The motive to increase the collection of cash waqf should be an important agenda in improving the beneficiaries’ socio economy and wellbeing, thus this study focus on three developed states which are Selangor, Kuala Lumpur and Johor. The study focus on technology acceptance among Muslims in these three states with their intention to contribute cash waqf. This study is based on the data obtained from a survey using structured questionnaire involving employed Muslims in Selangor, Kuala Lumpur and Johor which constitute the highest employed people with the highest income and payment salary, as well as the highest collection of cash waqf. Data collected from 316 respondents were analysed using PLS-SEM. The results show that technology acceptance was positively significant in influencing the intention to contribute cash waqf. Thus, this study emphasizes the role of technology that needs to be implemented aggressively in cash waqf collection to increase contributions among Muslims in Malaysia. In addition, various ways to enhance contribution of cash waqf are also provided.